THE EFFECT OF INTERNALIZATION OF VALUES OF ENTREPRENEURSHIP, SKILLS AND TRUST IN SELF TO THE INTENTION OF BUSINESS ENTREPRENEURS OF MADRASAH ALIYAH STUDENTS IN BANYUWANGI - Excellent, Fitriani; harti; Seno, Tony (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2022)
This study aims to analyze: 1) whether there is an influence of internalization of entrepreneurial values ??on entrepreneurial intentions. 2) whether there is an influence of skills on entrepreneurial intentions. 3) whether there is an effect of self confidence on entrepreneurial intentions, and 4) whether there is an influence of internalization of entrepreneurial values, skills and confidence in the entrepreneurial intentions of Madrasah Aliyah students in Banyuwangi. The approach in this study uses a quantitative research approach. This study uses primary data obtained from questionnaire answers to class XII students totaling 204 respondents, the sampling technique uses simple random sampling. Based on the results of data analysis, the results of the study show that partially (1) there is a significant influence on the internalization of entrepreneurial values ??on entrepreneurial intentions; (2) there is a significant influence of entrepreneurial skills on entrepreneurial intentions; and (3) there is a significant influence of self confidence on the entrepreneurial intentions of Madrasah Aliyah students in Banyuwangi. F Test Results obtained a significance value of 0.00 <0.05, this can be interpreted that the influence of internalization of entrepreneurial values, skills and self-confidence together influence the entrepreneurial intentions of Madrasah Aliyah students in Banyuwangi.   Keywords: internalization of entrepreneurial values, skills, self-confidence, entrepreneurial intentions